2021
DOI: 10.1007/s12265-021-10143-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Fluid-Structure Interaction in Extracorporeal Membrane Oxygenation Circulatory Support Systems

Abstract: Extracorporeal membrane oxygenation (ECMO) is a vital mechanical circulatory support modality capable of restoring perfusion for the patient in circulatory failure.Despite increasing adoption of ECMO there is incomplete understanding of its effects on systemic hemodynamics and how the vasculature responds to varying levels of continuous retrograde perfusion. To gain further insight into the complex ECMO:failingheart circulation, computational fluid dynamics simulations focused on perfusion distribution and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…33 As reported by Seethararam and colleagues, complex flow features, including unsteady swirling, vortical flows, are encountered through the aorta due to the interaction between pulsatile cardiac flow and steady-state ECMO. 18 In our current study we found that the location of disturbed flow, and high wall shear stress co-localized with the insertion site of the arterial cannula, confirming previous findings by Nezami et al 22 The peak oscillatory shear was located around the arterial cannula in the AAC and SAC model, most likely due to local recirculation of flow. The peak OSI for the FAC model was located in close proximity to the flow mixing zone the aortic arch.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…33 As reported by Seethararam and colleagues, complex flow features, including unsteady swirling, vortical flows, are encountered through the aorta due to the interaction between pulsatile cardiac flow and steady-state ECMO. 18 In our current study we found that the location of disturbed flow, and high wall shear stress co-localized with the insertion site of the arterial cannula, confirming previous findings by Nezami et al 22 The peak oscillatory shear was located around the arterial cannula in the AAC and SAC model, most likely due to local recirculation of flow. The peak OSI for the FAC model was located in close proximity to the flow mixing zone the aortic arch.…”
Section: Discussionsupporting
confidence: 91%
“…16,17 More specifically, CFD analyses have been used to provide a mechanistic interpretation of ECMO, including the impact of varying flow rates on differential hypoxemia, flow mixing phenomena, and neurological complications related to ECMO. [18][19][20][21][22] In this work on adult ECMO, we evaluated global and regional hemodynamics in a 56-year-old patient on peripheral VA-ECMO following acute cardiopulmonary failure using a patient-specific CFD analysis, where we explored the hemodynamic alterations introduced by different ECMO configurations, and identified contributions of pulsatile cardiac and nonpulsatile ECMO flows to various endorgan vascular beds.…”
Section: Calibration We Augmented the 3d Geometrical Model To Represe...mentioning
confidence: 99%
“…Various studies have previously investigated mixing zone location during VA ECMO using a CFD model [7][8][9][10][11]. However, these studies primarily involved variation of VA ECMO ow rates with a constant cannula position throughout.…”
Section: Clinical Interventions For Preventing Cerebral Hypoxia Inclu...mentioning
confidence: 99%
“…Incorporating wall deformability would require much higher computational power than was feasible for the number of simulations conducted. However, Nezami et al included wall deformability and their mixing zone results showed negligible difference to simulations conducted with rigid vessel walls [9]. Secondly, the resistance and compliance parameters used in the Windkessel model re ect healthy patient conditions.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation